A Monitoring Program to Evaluate the Coastal Grassland Restoration Incentive Program - Stephen J DeMaso; William G Vermillion; Mark W Parr (National Quail Symposium Proceedings, 2022)
The Gulf Coast Joint Venture (GCJV) is a regionally based, biologically driven, landscape-oriented volunteer partnership of private, state, and federal conservation organizations dedicated to the delivery of habitat important to priority bird species. The GCJV partnership’s Coastal Grassland Restoration Incentive Program (C-GRIP) provides financial incentives to private landowners for conducting habitat treatments that address the greatest limiting factor(s) to providing suitable grassland bird habitat on their property. The C-GRIP program is a way for the GCJV to deliver bird habitat to meet planning objectives for grassland birds, including northern bobwhite (Colinus virginianus). Our monitoring objective is to evaluate whether the C-GRIP program is effective in providing a relative increase in the density (number/acre) of priority grassland bird species in focal delivery areas versus control areas over a 10-year period. Twenty survey routes (2 within each of 5 focal areas and 2 outside of each area, serving as controls), located on secondary and tertiary roads, were designated in the Texas Mid-Coast Initiative Area of the GCJV. Each route is 15 miles long and the land cover is similar along all survey routes. Each route has ≥30 point-count stations separated by ≥0.5 mile. We recognize that some routes will experience increased development over time, especially in counties neighboring large population centers such as Houston and Victoria. The plan is to continue to monitor these routes, as long as safety concerns do not increase. Survey data will be analyzed using Program Distance 7.3, release 1. Our poster will include details about the monitoring objective, survey route selection, and survey methods.
Keywords: Colinus virginianus; density; distance sampling; Gulf Coast Joint Venture; habitat delivery; monitoring